If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + 15 = 3(3z + -2) + 9 + z Reorder the terms: 15 + 3z = 3(3z + -2) + 9 + z Reorder the terms: 15 + 3z = 3(-2 + 3z) + 9 + z 15 + 3z = (-2 * 3 + 3z * 3) + 9 + z 15 + 3z = (-6 + 9z) + 9 + z Reorder the terms: 15 + 3z = -6 + 9 + 9z + z Combine like terms: -6 + 9 = 3 15 + 3z = 3 + 9z + z Combine like terms: 9z + z = 10z 15 + 3z = 3 + 10z Solving 15 + 3z = 3 + 10z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-10z' to each side of the equation. 15 + 3z + -10z = 3 + 10z + -10z Combine like terms: 3z + -10z = -7z 15 + -7z = 3 + 10z + -10z Combine like terms: 10z + -10z = 0 15 + -7z = 3 + 0 15 + -7z = 3 Add '-15' to each side of the equation. 15 + -15 + -7z = 3 + -15 Combine like terms: 15 + -15 = 0 0 + -7z = 3 + -15 -7z = 3 + -15 Combine like terms: 3 + -15 = -12 -7z = -12 Divide each side by '-7'. z = 1.714285714 Simplifying z = 1.714285714
| 4(4m-8)=8(2m-3) | | 8y-16+5y=-29 | | 96t-16t^2=128 | | b*2=32 | | 2x+6=20x | | x^2+18x+80=0 | | ln(x-4)+ln(4x+1)=5 | | -7(h+1)=5(h-2) | | 18x^3+16x^2-10x= | | 10x-7=35x+3 | | 8x+3=12+9x | | 3k+15=6 | | 9p^2-12p-5= | | -2x+2x= | | 6x-12=-9x+13 | | 5a+8=5a-4 | | 2.5(6x-7)+1.33(2+9x)= | | (5a+8)=(5a-4) | | 19-0.25(x+8)=-1x+2 | | -5+x=-16 | | 2x^3+3x^2-11x-6=0 | | -5x^2+105=0 | | 7(x+.5)=-1.5(x+3x) | | 38m-6=14-2m | | 3x+10x=39 | | X-18.225=1.975 | | X=100+(X*0.05) | | 11x^2-32x-3= | | (3x-7)(5x-1)=y | | 6z-17z=22 | | 3x+6=30+7x | | 125m-100m+42750=45675-200m |